Targeting the Substrate Binding Site of E. coli Nitrile Reductase QueF by Modeling, Substrate and Enzyme Engineering. Issue 22 (17th April 2013) - Wilding, Birgit; Winkler, Margit; Petschacher, Barbara; Kratzer, Regina; Egger, Sigrid; Steinkellner, Georg; Lyskowski, Andrzej; Nidetzky, Bernd; Gruber, Karl; Klempier, Norbert
Abstract Nitrile reductase QueF catalyzes the reduction of 2‐amino‐5‐cyanopyrrolo[2, 3‐d]pyrimidin‐4‐one (preQ0) to 2‐amino‐5‐aminomethylpyrrolo[2, 3‐d]pyrimidin‐4‐one (preQ1) in the biosynthetic pathway of the hypermodified nucleoside queuosine. It is the only enzyme known to catalyze a reduction of a nitrile to its corresponding primary amine and could therefore expand the toolbox of biocatalytic reactions of nitriles. To evaluate this new oxidoreductase for application in biocatalytic reactions, investigation of its substrate scope is prerequisite. We report here an investigation of the active site binding properties and the substrate scope of nitrile reductase QueF from Escherichia coli. Screenings with simple nitrile structures revealed high substrate specificity. Consequently, binding interactions of the substrate to the active site were identified based on a new homology model of E. coli QueF and modeled complex structures of the natural and non‐natural substrates. Various structural analogues of the natural substrate preQ0 were synthesized and screened with wild‐type QueF from E. coli and several active site mutants. Two amino acid residues Cys190 and Asp197 were shown to play an essential role in the catalytic mechanism. Three non‐natural substrates were identified and compared to the natural substrate regarding their specific activities by using wild‐type and mutant nitrile reductase.